RNA silencing proteins and small RNAs in oomycete plant pathogens and biocontrol agents - Piombo, Edoardo; Kelbessa, Bekele Gelena; Sundararajan, Poorva; Whisson, Stephen C.; Vetukuri, Ramesh Raju; Dubey, Mukesh (Frontiers in Microbiology, 2023)
Introduction Oomycetes cause several damaging diseases of plants and animals, and some species also act as biocontrol agents on insects, fungi, and other oomycetes. RNA silencing is increasingly being shown to play a role in the pathogenicity of Phytophthora species, either through trans-boundary movement of small RNAs (sRNAs) or through expression regulation of infection promoting effectors. Methods To gain a wider understanding of RNA silencing in oomycete species with more diverse hosts, we mined genome assemblies for Dicer-like (DCL), Argonaute (AGO), and RNA dependent RNA polymerase (RDRP) proteins from Phytophthora plurivora, Ph. cactorum, Ph. colocasiae, Pythium oligandrum, Py. periplocum, and Lagenidium giganteum. Moreover, we sequenced small RNAs from the mycelium stage in each of these species. Results and discussion Each of the species possessed a single DCL protein, but they differed in the number and sequence of AGOs and RDRPs. SRNAs of 21nt, 25nt, and 26nt were prevalent in all oomycetes analyzed, but the relative abundance and 5’ base preference of these classes differed markedly between genera. Most sRNAs mapped to transposons and other repeats, signifying that the major role for RNA silencing in oomycetes is to limit the expansion of these elements. We also found that sRNAs may act to regulate the expression of duplicated genes. Other sRNAs mapped to several gene families, and this number was higher in Pythium spp., suggesting a role of RNA silencing in regulating gene expression. Genes for most effector classes were the source of sRNAs of variable size, but some gene families showed a preference for specific classes of sRNAs, such as 25/26 nt sRNAs targeting RxLR effector genes in Phytophthora species. Novel miRNA-like RNAs (milRNAs) were discovered in all species, and two were predicted to target transcripts for RxLR effectors in Ph. plurivora and Ph. cactorum, indicating a putative role in regulating infection. Moreover, milRNAs from the biocontrol Pythium species had matches in the predicted transcriptome of Phytophthora infestans and Botrytis cinerea, and L. giganteum milRNAs matched candidate genes in the mosquito Aedes aegypti. This suggests that trans-boundary RNA silencing may have a role in the biocontrol action of these oomycetes.